Conrad Shawcross - Psychogeometries - Shawcross, Conrad 1977- (Elephant, 2018)
This work considers the conceptual, thematic, and material development of Shawcross's art, from the extraordinary machines that marks his emergence in the early 2000s to his most recent projects, which extend the possibilities of art in the public realm
Keywords: Shawcross, Conrad -- 1977-; Plastik; Shawcross, Conrad; Sculpture, British / 21st century; Geometry in art; Sculpture, British; 2000-2099; Bildband